Large‐Area and Low‐Cost Nanoslit‐Based Flexible Metasurfaces for Multispectral Electromagnetic Wave Manipulation. Issue 23 (2nd September 2019) - Zhang, Ming; Ma, Xiaoliang; Pu, Mingbo; Liu, Kaipeng; Guo, Yinghui; Huang, Yijia; Xie, Xin; Li, Xiong; Yu, Honglin; Luo, Xiangang
Abstract: Manipulating multispectral electromagnetic (EM) waves has drawn great attention due to its potential applications in EM compatibility, radiative cooling, and multispectral imaging. Metasurfaces are intensively investigated to control EM waves and achieve versatile functions. However, the design of multispectral manipulation and the fabrication of multiscale metasurfaces remain a great challenge. Here, a multiscale flexible metasurface with nanometer‐sized characteristic dimensions and a square centimeter sized area is designed and fabricated for the simultaneous manipulation of infrared and terahertz waves. A simple yet powerful analytic method derived from catenary field theory is proposed to guide the design. A metasurface consisting of 2D nanoslit array is fabricated onto a flexible polyimide substrate by combining shadow mask fabrication with surface plasmon lithography to achieve nanoscale, large‐area, and repeatable fabrication. The experimental results show that the proposed metasurface possesses high reflectance exceeding 95% within the 8–12 µm wavelength range, indicating low thermal emissivity. Additionally, the metasurface exhibits low reflection in the THz regime and is capable of implementing integrated functions in conjunction with THz devices. Furthermore, the significant advantage of flexibility affords the metasurface excellent compatibility with irregular surfaces. This work may provide important guidance for the design and fabrication of large‐scale multispectral metasurfaces. Abstract : Manipulating multispectral electromagnetic waves simultaneously shows great potential in electromagnetic compatibility. Here, a multiscale flexible metasurface is designed based on catenary model and fabricated by combining shadow fabrication with SP lithography for realizing simultaneous manipulation of infrared and terahertz waves. This work can provide important guidance for design and fabrication of large‐scale and low‐cost multispectral manipulation materials.